(3EbdjejI VQjHI GdONd ai GdbGfhf GdYQGbj (B:s (3OQGSI ebGQfI (B/s - (3YHO GdMSf gGOj UGdMs; (3YGWa UObjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1983)
(3JbJUQ gPg GdOQGSI ebGQfI hbGUQI Ydi HYV bhGfjf GdOhd hCgegG GdbGfhf GdeUQj hGdbGfhf GdaQfSj hGdbGfhf GdEfLdjRj hGdbGfhf GdCeQjcj hjJUOQ GdHMK HGH JegjOj aj aUdjf jNJU GdChd HGdCSS GdeYGUQI HaQV VQjHI GdONd, HjfeG jHMK GdKGfj ajeG jJQJH Ydi GNJdGa CSS aQV VQjHI GdONd, hHYO GdOQGSI GdJegjOjI jfbSe GdHMK Edi bSejf QFjSjjf, hYdi GdJaUjd GdJGdj(B: (3GdbSe GdChd jYGdL bhGYO JWHjb eHOC GdEbdjejI aj GdbGfhf GdYQGbj hGdbGfhf GdebGQf, hPdc aj HGHjf jHMK ChdgeG eHOC GdEbdjejI hjYGdL GdHGH GdKGfj GdbhGYO GdJj CNP HgG GdbGfhf GdebGQf aj JWHjb eHOC GdEbdjejI CeG GdbSe GdKGfj ef GdHMK agh NGU HbhGYO GdNQhL Ydi eHOC GdEbdjejI aj GdbGfhf GdYQGbj hGdbGfhf GdebGQf, hPdc aj HGHjf jYGdL ChdgeG GdbhGYO GdJj NQL HgG GdbGfhf GdYQGbj Ydi eHOC GdEbdjejI HjfeG jHMK GdHGH GdKGfj aj GdbhGYO GdJj NQLJ HgG HYV GdbhGfjf GdebGQfI Ydi eHOC GdEbdjejI(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdeGdjI GdYGeI hGdJTQjY GdVQjHj (B1983.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B441-457.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdVQGFHs -- (3bhGfjf hJTQjYGJs -- (3GdYQGbs; (3GdGROhGL GdVQjHjs; (3GdGSJZdGd GdJLGQjs; (3eHOC GdJHYjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjY GdVQjHjs